Temperature-dependent responses of the hard corals Acropora sp. and Pocillopora verrucosa to molecular hydrogen - Malte Ostendarp; Mareike de Breuyn; Yusuf C. El-Khaled; Neus Garcias-Bonet; Susana Carvalho; Raquel S. Peixoto; Christian Wild (PLoS ONE, 2025)
Coral reefs are increasingly threatened by mass bleaching events due to global ocean warming. Novel management strategies are urgently needed to support coral survival until global efforts can mitigate ocean warming. Given the strong antioxidant, anti-inflammatory and anti-apoptotic properties of molecular hydrogen, our study explores its potential to alleviate the negative effects of heat stress on corals. We investigated the ecophysiological responses of two common hard corals (Acropora sp. and Pocillopora verrucosa) from the Central Red Sea under ambient (26 °C) and elevated seawater temperatures (32 °C), with and without hydrogen addition ( ~ 150 µ M H2) over 48 h. Our results showed that at 32 °C without hydrogen addition, P. verrucosa exhibited high temperature tolerance, whereas Acropora sp. showed significant reductions in photosynthetic efficiency and maximum electron transport rate compared to the ambient condition (26 °C). The addition of hydrogen at 32 °C increased the maximum electron transport rate of Acropora sp. by 28%, maintaining it at levels compared to those at 26 °C. In contrast, the addition of hydrogen at 26 °C caused a significant decrease in the photophysiology of both Acropora sp. and P. verrucosa. This suggests that the short-term response of the coral holobiont to molecular hydrogen is temperature-dependent, potentially benefiting the coral holobiont under heat stress, while impairing the photophysiology under ambient temperatures. Our findings therefore provide the foundation for future long-term studies uncovering the mechanisms behind molecular hydrogen, potentially informing the development of new management strategies to enhance coral resilience to ocean warming.